f f(x) = 4 – x2 and g(x) = 6x, which expression is equivalent to (g – f)(3)?
6 – 3 – (4 + 3)2
6 – 3 – (4 – 32)
6(3) – 4 + 32
6(3) – 4 – 32

Respuesta :

Happil

Subtracting Functions

Answer:

[tex]6(3) -4 +3^2[/tex]

Step-by-step explanation:

Given:

[tex]f(x) = 4 -x^2[/tex]

[tex]g(x) = 6x[/tex]

Before we find the expression of [tex](g -f)(3)[/tex], we must first know how [tex](g -f)(x)[/tex] is defined.

[tex](g -f)(x) = g(x) -f(x) \\ (g -f)(x) = 6x -(4 -x^2) \\ (g -f)(x) = 6x +x^2 -4 \\ (g -f)(x) = x^2 +6x -4[/tex]

Now we can find [tex](g -f)(x)[/tex].

[tex](g -f)(3) = (3)^2 +6(3) -4[/tex]

sana makatulong pooooo

Ver imagen kiank4778
ACCESS MORE